PENINGKATKAN PENGETAHUAN KELUARGA TENTANG MENCEGAH PENULARAN PENYAKIT DBD DI RT 029/RW 010 WILAYAH KERJA PUSKESMAS HALONG - hani tuasikal (Universitas Islam Negeri Alauddin Makassar, 2018)
The rise of dengue cases that are happening then from the government and the Health Service in collaboration with Halong Community Health Center staff in handling DHF in Halong, among others, Preventing transmission of dengue disease by giving abate powder and if there are 2 cases of DHF in 1 RT then from Halong Health Center itself will do Fogging. This study aims to find out family knowledge about preventing transmission of dengue fever in RT 029 / RW 010 Halong Puskesmas Work Area. This research method is a descriptive case study. The population of this research is the family of Mr.K. The sample of this study was 3 family members. This research variable is the level of family knowledge about Preventing Transmission of Dengue Fever in RT 029 / RW 010 Work Area of Halong Health Center. Collected using a questionnaire with a total of 10 questions. The research results obtained were processed by tabulating and analyzed in percentage. Judging from the results of the pre-test respondents (46.6%) lack of knowledge, (80%) good knowledge.